The Relationship Between Depression Levels and Physical Activity with Hypertension Among the Elderly at Institutional Care Surabaya - Ines Aulia Latifah; Farapti Farapti; Eveline Gracela; Zuraini Mat Issa (Universitas Airlangga, 2026)
Introduction: Hypertension in the elderly can be influenced by several factors, including a lack of physical activity. Older adults with low physical activity levels tend to engage in monotonous daily routines, which may negatively affect their mental health by increasing stress levels. Prolonged stress can increase the risk of depression among older adults. Aim: To examine the relationship between depression levels, physical activity, and hypertension in older adults. Methods: This analytical observational study had a cross-sectional design and involved 63 proportionally selected participants through random sampling. Data collection included questionnaires to assess depression levels and physical activity, as well as blood pressure measurements. The study was conducted from May to June 2024 at a public institutional care facility in Surabaya. Results: A significant correlation was found between physical activity levels and hypertension (p = 0.000; OR = 62.000), whereas depression levels showed no significant relationship with hypertension (p = 0.515). Conclusion: Based on these findings, it can be concluded that hypertension in older respondents is significantly associated with daily physical activity levels, although depression levels do not appear to be related to hypertension in this population.